Decrease in climatic conditions favouring floods in the south‐east of Belgium over 1959–2010 using the regional climate model MAR. (20th September 2016) - Wyard, Coraline; Scholzen, Chloé; Fettweis, Xavier; Van Campenhout, Jean; François, Louis
ABSTRACT: The Ourthe River, in the south‐east of Belgium, has a catchment area of 3500 km 2 and is one of the main tributaries of the Meuse River. In the Ourthe, most of the flood events (FE) occur during winter and about 50% of them are due to heavy rainfall events combined with an abrupt melting of the snowpack covering the Ardennes massif during winter. This study aims to determine whether trends in extreme hydroclimatic events generating floods can be detected over the last century in Belgium, where a global warming signal can be observed. Hydroclimatic conditions favourable to floods were reconstructed over 1959–2010 using the regional climate model MAR ('Modèle Atmosphérique Régional') forced by the ERA‐Interim/ERA‐40, the ERA‐20C and the NCEP/NCAR‐v1 reanalyses. Extreme run‐off events, which could potentially generate floods, were detected using run‐off caused by precipitation events and snowpack melting from the MAR model. In the validation process, the MAR‐driven temperature, precipitation and snow depth were successfully compared to daily weather data over the period 2008–2014 for 20 stations in Belgium. MAR also showed its ability to detect up to 90% of the hydroclimatic conditions which effectively generated observed floods in the Ourthe River over the period 1974–2010. Conditions favourable to floods in the Ourthe River catchment present a negative trend over the period 1959–2010 as a result of a decrease in snow accumulation and a shortening of the snow season. This trend is expected to accelerate in a warmer climate. However, regarding the impact of the extreme precipitation events evolution on conditions favouring floods, the signal is less clear because the trends depend on the reanalysis used to force the MAR model.